Learned stressor resistance requires extracellular signal-regulated kinase in the prefrontal cortex - Christianson, John P.; Flyer-Adams, Johanna G.; Drugan, Robert C.; Amat, Jose; Daut, Rachel A.; Foilb, Allison R.; Watkins, Linda R.; Maier, Steven F. (Frontiers in Behavioral Neuroscience, 2014)
Behaviorally controllable stressors confer protection from the neurochemical and behavioral consequences of future uncontrollable stressors, a phenomenon termed “behavioral immunization.” Recent data implicate neuroplasticity within the ventromedial prefrontal cortex (mPFC) as critical to behavioral immunization. Adult, male Sprague-Dawley rats were exposed to a series of controllable tailshocks and one week later to uncontrollable tailshocks, followed 24h later by social exploration and shuttlebox escape tests. To test the involvement of N-methyl-D-aspartate receptors (NMDAR) and the extracellular signal-regulated kinase (ERK) cascade in behavioral immunization, either D-AP5 or the MEK inhibitor U0126 was injected to the prelimbic (PL) or infralimbic (IL) mPFC prior to controllable stress exposure. Phosphorylated ERK and P70S6K, regulators of transcription and translation, were quantified by Western blot or immunohistochemistry after controllable or uncontrollable tailshocks. Prior controllable stress prevented the social exploration and shuttlebox performance deficits caused by the later uncontrollable stressor, and this effect was blocked by injections of D-AP5 into mPFC. A significant increase in phosphorylated ERK1 and ERK2, but not P70S6K, occurred within the PL and IL in rats exposed to controllable stress, but not to uncontrollable stress. However, U0126 only prevented behavioral immunization when injected to the PL. We provide evidence that NMDAR and ERK dependent plasticity within the PL region is required for behavioral immunization, a learned form of stressor resistance.